2015
DOI: 10.3892/or.2015.4511
|View full text |Cite
|
Sign up to set email alerts
|

3-Bromopyruvate and sodium citrate target glycolysis, suppress survivin, and induce mitochondrial-mediated apoptosis in gastric cancer cells and inhibit gastric orthotopic transplantation tumor growth

Abstract: Glycolysis is the primary method utilized by cancer cells to produce the energy (adenosine triphosphate, ATP) required for cell proliferation. Therefore, inhibition of glycolysis may inhibit tumor growth. We previously found that both 3-bromopyruvate (3-BrPA) and sodium citrate (SCT) can inhibit glycolysis in vitro; however, the underlying inhibitory mechanisms remain unclear. In the present study, we used a human gastric cancer cell line (SGC-7901) and an orthotopic transplantation tumor model in nude mice to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…Negative correlations between AEG‐1 and E‐cadherin, or positive correlations between AEG‐1 and vimentin, have been identified in hepatocellular carcinoma 44, lung cancer 45, laryngeal squamous cell carcinoma 46, squamous cell carcinoma of the head and neck 47 and osteosarcoma 48. Other studies have confirmed that overexpression or downregulation of AEG‐1 expression regulates EMT, migration or invasion in vitro in liver cancer cells 43, head and neck squamous cells 47, cervical cancer cells 49, and lung cancer cells 35, and in animal breast cancer models 50. However, similar studies on gastric cancer are lacking.…”
Section: Discussionmentioning
confidence: 93%
“…Negative correlations between AEG‐1 and E‐cadherin, or positive correlations between AEG‐1 and vimentin, have been identified in hepatocellular carcinoma 44, lung cancer 45, laryngeal squamous cell carcinoma 46, squamous cell carcinoma of the head and neck 47 and osteosarcoma 48. Other studies have confirmed that overexpression or downregulation of AEG‐1 expression regulates EMT, migration or invasion in vitro in liver cancer cells 43, head and neck squamous cells 47, cervical cancer cells 49, and lung cancer cells 35, and in animal breast cancer models 50. However, similar studies on gastric cancer are lacking.…”
Section: Discussionmentioning
confidence: 93%
“…The mitochondrial-dependent pathway is mainly regulated by the activity of Bcl-2 family, such as pro-apoptotic member Bax and anti-apoptotic member Bcl-224. Bax increases mitochondrial membrane permeability, causing the loss of mitochondrial membrane potential and the increased of intracellular ROS, which activates the caspase cascade and initiates cell apoptosis1425. Conversely, Bcl-2 stabilizes mitochondrial membrane permeability, thereby inhibiting apoptosis26.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a recent study reported that the glycolysis-relevant enzymes may be a promising target to inhibit cancer cell proliferation and induce cell apoptosis in gastric cancer cells9. Aerobic glycolysis is the primary metabolic way utilized by most tumor cells to produce adenosine triphosphate (ATP) for growth and proliferation10.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a glycolytic inhibitor, "3BP is a fast acting, promising, powerful, specific and effective anti-cancer agent", said by Pedersen 3 . Also 3BP has been identified to inhibit tumor cells proliferation as a proposed widely used anti-cancer agent 4 , such as in breast cancer cells 5,6 , liver cancer cells 7,8 , lymphoma cells 9 , lung cancer cells 10 , pancreatic cancer cells 11,12 , gastric cancer 2,13 , colorectal cancer cells 14 . Those significant anti-tumor effects of 3BP has made it getting more and more attention 15,16 .…”
mentioning
confidence: 99%